2012
DOI: 10.1111/j.1447-0756.2011.01740.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preeclampsia on the yield of hematopoietic stem cells obtained from umbilical cord blood at delivery

Abstract: Aim: To compare the numbers of cord blood CD34+ hematopoietic stem cells (HSC) between preeclampsia (PE) and control (non-PE) subjects and to determine the factors that may influence this observation. Methods: Umbilical cord blood was collected from 28 PE and 19 non-PE subjects. Nucleated and CD34+ cell counts were derived using the Trucount tube-based stem cell enumeration kit on BD FACSCalibur. Results: The cord blood volume, nucleated and CD34+ cell counts were significantly reduced in PE subjects compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Interestingly, we found no clinical correlation of premature birth associated morbidities on HSPC count and clonogenic capacity. In our study, preeclampsia and small-for-gestational-age did not affect the cord blood HSPC concentration as described by other groups [20], [29] and may be due to our small sample size. Although tocolysis with Atosiban had no effect on the HSPC population, the influence of magnesium sulfate on CD34+ cells, which is widely used as tocolytic drug in the U.S., is still unknown.…”
Section: Discussionsupporting
confidence: 60%
“…Interestingly, we found no clinical correlation of premature birth associated morbidities on HSPC count and clonogenic capacity. In our study, preeclampsia and small-for-gestational-age did not affect the cord blood HSPC concentration as described by other groups [20], [29] and may be due to our small sample size. Although tocolysis with Atosiban had no effect on the HSPC population, the influence of magnesium sulfate on CD34+ cells, which is widely used as tocolytic drug in the U.S., is still unknown.…”
Section: Discussionsupporting
confidence: 60%
“…45 Researchers have found that circulating endothelial progenitor cells in mothers with preeclampsia are lower and hepatic hematopoiesis of their fetuses are reduced. 46 Furthermore, inhibition of miR-142-3p distinctly promotes cell migration. 47 The MiR-142-3p may also participate in the inflammatory response by regulating the production of IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…However, in three previous studies, a decrease in the number of CD34+ cells in the preeclampsia group compared to the non-preeclampsia group was reported. [27][28][29] This difference may be due to our population size, which is less than two previous studies. Alternatively, although our patient group has pathologies of the same origin, our GHT group includes six pregnancy hypertension and five preeclampsia patients.…”
Section: Discussionmentioning
confidence: 66%
“…[6][7][8] Because of these restrictive problems, research in the literature has focused on factors altering CD34+ cells product such as maternal age, smoking status, birth weight, gestational age, gender, mode of delivery, preeclampsia. [9][10][11][12] Whereas the effect of morbidly adherent placenta (MAP) disease caused by abnormal implantation of the basal plate, 13 reported as 3% in women with previous cesarean history and 60% in women with three previous cesarean histories, MAP's impact on CD34+ cells 14 has not been demonstrated. 15 Also, there are not many articles on the effect of gestational diabetes mellitus (GDM) and gestational hypertension (GHT) diseases on the number of CD34+ cells in the umbilical cord blood, which are important diseases in obstetrics and gynecology practice.…”
Section: Introductionmentioning
confidence: 99%